INET Working Paper Series 2020
DOI: 10.36687/inetwp118
|View full text |Cite
|
Sign up to set email alerts
|

Private Equity Buyouts in Healthcare: Who Wins, Who Loses?

Abstract: Private equity firms have become major players in the healthcare industry. How has this happened and what are the results? What is private equity’s ‘value proposition’ to the industry and to the American people -- at a time when healthcare is under constant pressure to cut costs and prices? How can PE firms use their classic leveraged buyout model to ‘save healthcare’ while delivering ‘outsized returns’ to investors? In this paper, we bring together a wide range of sources and empirical evidence to answer thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 14 publications
0
63
0
Order By: Relevance
“…Patients are less likely to control which physicians treat them at the emergency room, increasing the likelihood that they will be charged high out-of-network and surprise bills ( Appelbaum & Batt, 2014 ; Cooper et al, 2020 ). Eileen Applebaum and Rosemary Batt (2020) found that bills from the health care groups Envision Healthcare and TeamHealth, owned by the private equity behemoths Blackstone and K.K.R., accounted for considerable increases in surprise medical bills. Private equity buyouts also have had negative impacts on patient health and compliance with care standards at nursing homes ( Gupta et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients are less likely to control which physicians treat them at the emergency room, increasing the likelihood that they will be charged high out-of-network and surprise bills ( Appelbaum & Batt, 2014 ; Cooper et al, 2020 ). Eileen Applebaum and Rosemary Batt (2020) found that bills from the health care groups Envision Healthcare and TeamHealth, owned by the private equity behemoths Blackstone and K.K.R., accounted for considerable increases in surprise medical bills. Private equity buyouts also have had negative impacts on patient health and compliance with care standards at nursing homes ( Gupta et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…11 The PE-owned hospitals are often the most debt-inflated providers. 12,13 Because of their high debt-to-equity ratios, they depend on a constant cashflow. Moreover, PE firms usually have short time horizons: they seek to sell companies with a decent profit after a limited period.…”
Section: Private Equity Owned Versus Publicly-quoted and Owner-managementioning
confidence: 99%
“…For example, HCA has a solvency rate of -13% in 2018 and Tenet Healthcare has a rate of -1%, whereas Universal Health Services has a rate of 48%. 5 (This may however be explained by the previous involvement of PE in HCA and Tenet Healthcare 13 ). Due to the pandemic, it will be more difficult for PQ hospitals to raise funds on the stock market.…”
Section: Private Equity Owned Versus Publicly-quoted and Owner-managementioning
confidence: 99%
See 2 more Smart Citations